2018
DOI: 10.1002/jbio.201800180
|View full text |Cite
|
Sign up to set email alerts
|

Optical palpation for the visualization of tumor in human breast tissue

Abstract: Accurate and effective removal of tumor in one operation is an important goal of breast-conserving surgery. However, it is not always achieved. Surgeons often utilize manual palpation to assess the surgical margin and/or the breast cavity. Manual palpation, however, is subjective and has relatively low resolution. Here, we investigate a tactile imaging technique, optical palpation, for the visualization of tumor. Optical palpation generates maps of the stress at the surface of tissue under static preload compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…OCT-based optical palpation is performed to provide a comparison to CBOP. This is achieved using a spectral-domain OCT system with central wavelength of 1,300 nm and spectral bandwidth of 170 nm (TEL320C1, Thorlabs, New Jersey, USA), in a common-path configuration 40 . An objective lens with a 0.055 numerical aperture (LSM03, Thorlabs, New Jersey, USA) is attached to the scan head which provides a measured full width at half maximum axial resolution of 5.5 µm (in air) and lateral resolution of 7.2 µm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…OCT-based optical palpation is performed to provide a comparison to CBOP. This is achieved using a spectral-domain OCT system with central wavelength of 1,300 nm and spectral bandwidth of 170 nm (TEL320C1, Thorlabs, New Jersey, USA), in a common-path configuration 40 . An objective lens with a 0.055 numerical aperture (LSM03, Thorlabs, New Jersey, USA) is attached to the scan head which provides a measured full width at half maximum axial resolution of 5.5 µm (in air) and lateral resolution of 7.2 µm.…”
Section: Methodsmentioning
confidence: 99%
“…The strain in the layer is determined by the thickness change measured from the OCT data and the known stress-strain relationship is then used to generate optical palpograms. OCT-based optical palpation has been demonstrated to provide high imaging contrast for skin and human breast tissue 39,40 . For example, in one study of excised human breast tissue from 34 patients, strong correlation was observed between optical palpograms and corresponding gold standard histology 40 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated regions of stress indicate stiffer underlying features, thus if compression is kept approximately constant between samples, stress may be used to distinguish tissue types. Particularly in turbid tissues, where optical contrast alone is often insufficient to distinguish features of interest [18], optical palpation has been demonstrated to enhance visualization by providing complementary mechanical contrast [19,9]. Importantly, as optical palpation does not rely on dense oversampling, as is the case with phase-sensitive approaches [15,20], acquisition times can be as rapid as in standard 3D-OCT.…”
mentioning
confidence: 99%
“…Importantly, as optical palpation does not rely on dense oversampling, as is the case with phase-sensitive approaches [15,20], acquisition times can be as rapid as in standard 3D-OCT. In addition, as optical palpation provides en face images, it enables large surface areas (up to 16 × 16 mm [19]) to be scanned in one acquisition.…”
mentioning
confidence: 99%